Relações raciais e memória : um estudo sobre o processo escolar e seus aspectos psicossociais na construção da identidade negra - Souza, Emanuelle Carine da Silva (2019)
The resulting dissertation from this research has as its object the psychosocial aspects of the school process in the construction of black identity. In taking the psychosocial aspects of the school process, we mean the junction of the psychological and the social as inseparable forms to conceive the constitution of the human being, and of how the school has direct interferences in this movement, recognizing it as an institution that forms social individuals. The research has as main areas of interlocution Racial Relations and Education interfacing with Psychology; thus its general objective is to understand the psychosocial aspects of the school process in the construction of the identity of black subjects (a) of the city of Cuiabá - MT, and as specific objectives (1) Identify the meanings of black identity from the use of orality; (2) Understand the social relations around the black identity in the school environment; (3) To discuss the implications of this black identity construction in everyday life. The research was developed under a qualitative approach, using oral history as a methodology, since it allows retelling the history through direct contact with the historical source, as well as recording it from recordings and transcriptions. The semi-structured interview is used here as the main instrument of data collection. For analysis, content analysis was used as a technique, through which it is possible to describe and interpret the content raised from the interviews. The research was carried out in the city of Cuiabá, with nine self-declared black or brown participants, over 18, who were aware of the research in the first moment by invitation triggered in social networks and in exchange applications of messages. The interview made it possible to know the stories and crossings faced by the participants within the school process, regarding the construction of their racial identity, and how much the school plays a fundamental role for the formation of black men and women conscious of their histories, of how racism can have negative consequences in their lives, and also of the importance of Racial Relations Education and the Law 10.639 / 03 as sources of support for the creation of strategies to combat this type of violence and for the affirmation of these students identities - in the search for an anti-racist society.